Development of interactive learning media based on websites for the textile science course - Adelia Chairun Nisa; Arismunandar Arismunandar; Arnidah Arnidah (Himpunan Pengembang Kurikulum Indonesia, 2025)
The development of science and technology changes the learning process from several aspects, including textile science courses. This research aims to develop interactive learning media in textile science courses. This research was conducted using the RnD approach by adapting the ADDIE model. The subjects of this study consisted of material validators, media validators, and 31 students of the Family Welfare Education Department. Data collection used interviews, needs identification questionnaires, material and design validation questionnaires, small group trials, pretests, and posttests. Data analysis techniques were carried out descriptively and qualitatively for interview results and quantitatively for questionnaire results. The results of this study found that the identification of student needs reached a score of 60 percent. Interactive learning media development design is designed using Canva, Google Drive, and Google Sites, which can be integrated using a laptop device. The level of validity of Interactive Learning Media material is 4.5 and media 4.7 at the valid qualification stage. The level of practicality obtained from the pre-test and post-test results reached 93 percent. It can be concluded that the learning media that have been developed are very effective. Abstrak Perkembangan ilmu pengetahuan dan teknologi memberikan perubahan dalam proses pembelajaran dari beberapa aspek, termasuk pada mata kuliah ilmu pengetahuan tekstil. Penelitian ini bertujuan untuk mengembangkan media pembelajaran interaktif pada mata kuliah ilmu pengetahuan tekstil. Penelitian ini dilakukan menggunakan pendekatan RnD dengan mengadaptasi model ADDIE. Subjek penelitian ini terdiri dari validator materi, validator media, dan mahasiswa Jurusan Pendidikan Kesejahteraan Keluarga berjumlah 31 orang. Pengumpulan data menggunakan wawancara, angket identifikasi kebutuhan, angket validasi materi dan desain, uji coba kelompok kecil, pretest, dan posttest. Teknik analisis data dilakukan secara deskriptif kualitatif untuk hasil wawancara dan kuantitatif untuk hasil angket. Hasil penelitian ini menemukan identifikasi kebutuhan mahasiswa mencapai skor 60 persen. Desain pengembangan media pembelajaran Interaktif dirancang menggunakan Canva, Google Drive, Google Site yang dapat diintegrasikan menggunakan perangkat laptop. Tingkat kevalidan Media Pembelajaran Interaktif materi yaitu 4,5 dan media 4,7 pada tahap kualifikasi valid. Hasil tingkat kepraktisan yang diperoleh dari berdasarkan hasil pre-test dan post-test mencapai 93 persen. Dapat disimpulkan bahwa media pembelajaran yang telah dikembangkan sangat efektif. Kata Kunci: ADDIE Model; ilmu pengetahuan tekstil; pembelajaran interaktif; pengembangan media